Association between oxidative balance score and hearing loss: a cross-sectional study from the NHANES database - Zhou, Zhongming; Han, Yanyan (Frontiers in Nutrition, 2024)
The oxidative balance score (OBS), a composite score of dietary nutrients and lifestyles, reflects an individual's oxidative and antioxidant status. Evidence showed that oxidative stress levels were related to hearing loss. The relationship between OBS and hearing loss remains unclear. This study was to explore the association between OBS and hearing loss in adults.In this cross-sectional study, data of participants aged 20-69 years who received hearing tests were extracted from the National Health and Nutrition Examination Survey (NHANES) database (2011)(2012)(2015)(2016). Hearing loss was defined as hearing threshold >25 dB in either ear. The OBS was composed of 16 dietary nutrients and 4 lifestyles. The covariates were screened using the backward stepwise regression analysis. The association of OBS and hearing loss was assessed with odds ratios (ORs) and 95% confidence intervals (CIs). Subgroups of age, gender, occupational noise exposure, recreational noise exposure, firearm noise exposure, and veteran status were further evaluated the associations. The importance ranking of OBS components was analyzed by the weighted random forest model.Of the total 3,557 adults, 338 (9.5%) suffered from hearing loss. High OBS levels were associated with lower odds of hearing loss (OR=0.58, 95%CI: 0.41-0.82), after adjusting age, gender, race, hypertension, tinnitus, recreational noise exposure, and occupational noise exposure. Similar results were discovered in individuals aged 50-59 years old (OR=0.47, 95%CI: 0.24-0.93), aged 60-69 years old (OR=0.31, 95%CI: 0.16-0.61), with female (OR=0.44, 95%CI: 0.20-0.96), without occupational noise Association between OBS and hearing loss exposure (OR=0.31, 95%CI: 0.16-0.62), recreational noise exposure (OR=0.48, 95%CI: 0.30-0.76), firearm noise exposure (OR=0.38, 95%CI: 0.19-0.77), and veteran status (OR=0.57, 95%CI: 0.39-0.82). In OBS components, vitamin B12, total fat and physical activity were important for hearing loss.Elevated OBS may be associated with hearing health in adults.Appropriate vitamin B12 supplementation, reduction of total fat intake, and increased physical activity may be beneficial to the prevention of hearing loss.